2019
DOI: 10.1002/hpm.2758
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of nasal continuous airway pressure therapy in patients with obstructive sleep apnea

Abstract: Summary Objectives A prospective observational study was carried out with the aim of evaluating the effectiveness of nasal continuous positive airway pressure (nCPAP) therapy on the health‐related quality of life (QoL) of patients with obstructive sleep apnea (OSA). Methods The patients included in this study were those recently diagnosed with OSA (AHI > 5) and given nCPAP therapy, as well as being referred to a sleep laboratory for an assessment of their sleep disordered breathing. Prior to the start of nCPAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Moreover, over a 4-year period, the Wisconsin Sleep Cohort Study revealed that for every 1% change in weight, OSA severity changed by about 3% [ 48 ]. According to a prior study, the severity of AHI was found to be correlated with all SpO2 measures ( p < 0.001) [ 49 ]. Recent research suggests that the “hypoxic burden (HB)” specific to sleep apnea, which is the total of individual regions under the oxygen desaturation curve, may be useful in identifying high-risk OSA sufferers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, over a 4-year period, the Wisconsin Sleep Cohort Study revealed that for every 1% change in weight, OSA severity changed by about 3% [ 48 ]. According to a prior study, the severity of AHI was found to be correlated with all SpO2 measures ( p < 0.001) [ 49 ]. Recent research suggests that the “hypoxic burden (HB)” specific to sleep apnea, which is the total of individual regions under the oxygen desaturation curve, may be useful in identifying high-risk OSA sufferers.…”
Section: Discussionmentioning
confidence: 99%